2019
DOI: 10.1016/j.cogsys.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of task constraint on action dynamics

Abstract: The actualization of action possibilities (i.e., affordances) can often be accomplished in numerous ways. For instance, an individual could walk over to a rubbish bin to drop an item in or throw the piece of rubbish into the bin from some distance away. The aim of the current study was to investigate the action dynamics that emerge from such under-constrained task or action spaces using an object transportation task. Participants were instructed to transport balls between a starting location and a large wooden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The reaching task in VR produced highly variable action patterns that could be classified into four general classes of solutions, similar to the ones found in Nordbeck et al (2019) with the exception that the most extreme ends were not found in this particular setup. Also, the time-series mimicked those of the previous task as well as the model simulations.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The reaching task in VR produced highly variable action patterns that could be classified into four general classes of solutions, similar to the ones found in Nordbeck et al (2019) with the exception that the most extreme ends were not found in this particular setup. Also, the time-series mimicked those of the previous task as well as the model simulations.…”
Section: Resultsmentioning
confidence: 59%
“…The two variables were then used to classify the time-series into one of four general solution types that vary in sensitivity to contextual conditions (see Figure 2). Exemplar time-series of the different solutions are plotted in Figure 3 along with comparison solutions (participant and simulated) from Nordbeck et al (2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cusp catastrophe theory is now widely used in research in behavior dynamics. 45 Some scholars considered two control variables: external workplace and internal psychological factors. 46 Scholars explored the effect of job tension and group cohesion on the sudden withdrawal behavior of nurses, stating that the cusp catastrophe model explains the behavior turnover of employees better than the linear regression model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To understand how interpersonal interactions are reflected on different levels of analysis, joint action should be studied with a more comprehensive multi-person approach that goes beyond hyperbrain scanning and integrates the assessment of neural signal synchrony and between-brain functional connectivity with the simultaneous monitoring of physiological responses (i.e., muscle activation, cardiac activity, and respiration), movement kinematics, and psychological states. A manipulation of joint action difficulty should be also considered to investigate how the complex system composed of the network of organs of two interacting individuals dynamically adjusts to variable external conditions ( Rocca and Cavallo, 2018 ; Nordbeck et al, 2019 ). By doing so, both overt and covert processes occurring during interpersonal coordinated actions can be analyzed.…”
Section: Introductionmentioning
confidence: 99%